Cruise Tourists in Spitsbergen around 1900: Between Observation and Transformation - Spring, Ulrike (Nordlit, 2020)
This article examines the early commodification of the Arctic, using emerging cruise tourism to Spitsbergen as an example. Its objective is to investigate how an Arctic tourism discourse emerged around 1900 and what its central characteristics were. Covering the period between 1893, when German Arctic cruise tourism took off, and 1914, the article argues that early cruise tourists drew on exploration, adventure and leisure discourses in order to frame their experiences. However, unlike explorers and explorer travellers (Laing and Frost 2014), they wished only to a limited extent to experience adventure themselves, or report transformative experiences due to the sublime landscape; rather, the travel narratives indicate that they were interested above all in observing adventure, this process being facilitated by the advanced technology and luxurious lifestyle of the cruise ships. As the article demonstrates, this ambivalence between images of a wild, uncontrolled and sublime Arctic and an Arctic controlled by modern technology and modern life helped to map the Arctic as a tourism space.